Epidemiology of 10 Cancer Types in Indonesia: A Multicenter Study - Jayalie, Vito Filbert; Gondhowiardjo, Soehartati; Kotambunan, Charity; Apriantoni, Riyan; Manuain, Donald Arinanda; Hawariy, Salik; Prajogi, Gregorius Ben; Permata, Tiara Bunga Mayang; Handoko, Handoko; Munandar, Arie; Sekarutami, Sri Mutya (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2023)
Cancer remains one of the largest contributors to the burden of health and mortality around the world. A study estimated 19.3 million new cases of cancer in the year 2020. GLOBOCAN 2020 provides a list of the most common cancers in the world which are prostate, lung, and colorectal cancers in men and breast, colorectal, and lung cancer in women. Naturally, different sociodemographic and geographic characteristics will cause disparities in these estimates. Since valid epidemiological data on cancer types in Indonesia remains unavailable, this study intended to provide data on the pattern of distribution of the 10 most common cancer types amongst various hospitals in Indonesia. This was achieved through the collection of registries and/or medical records that were obtained from March to September 2022. The data were then sorted and analyzed using SPSS 20.0. The resulting epidemiological data in multi-centers in Indonesia yielded a similar top 10 most common cancers trend with the GLOBOCAN 2020 worldwide incidence, although some differences were seen. A universal similarity that is found amongst different databases seems to be the prevalence of breast cancers, which always ‘champions’ all databases as the most common cancers among women. This provides a reflection for policy and decision makers for their prompt action to promote the prevention, diagnosis, and treatment of cancers in Indonesia, especially breast cancers.